2013
DOI: 10.1038/onc.2013.179
|View full text |Cite
|
Sign up to set email alerts
|

Brd4 maintains constitutively active NF-κB in cancer cells by binding to acetylated RelA

Abstract: Acetylation of the RelA subunit of NF-κB at lysine-310 regulates the transcriptional activation of NF-κB target genes and contributes to maintaining constitutively active NF-κB in tumors. Bromodomain-containing factor Brd4 has been shown to bind to acetylated lysine-310 and to regulate the transcriptional activity of NF-κB, but the role of this binding in maintaining constitutively active NF-κB in tumors remains elusive. In this study, we demonstrate the structural basis for the binding of bromodomains of Brd4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
230
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(259 citation statements)
references
References 51 publications
19
230
3
Order By: Relevance
“…Inhibition of BET family proteins by small molecules such as JQ1 and I-BET has been shown to down-regulate the expression of inflammatory genes selectively (16,19,20). To understand better the specific contribution of Brd4 in LPS-stimulated gene expression, we performed geneexpression microarray analysis using RNA isolated from WT and Brd4-deficient BMDMs stimulated or not stimulated by LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of BET family proteins by small molecules such as JQ1 and I-BET has been shown to down-regulate the expression of inflammatory genes selectively (16,19,20). To understand better the specific contribution of Brd4 in LPS-stimulated gene expression, we performed geneexpression microarray analysis using RNA isolated from WT and Brd4-deficient BMDMs stimulated or not stimulated by LPS.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of Brd4 by small molecules suppresses NF-κB-dependent inflammatory gene expression and LPS-induced sepsis (16,(18)(19)(20). Brd4 also has been shown to regulate inflammatory gene expression by facilitating the transcription of enhancer RNA and super-enhancer formation (14,16,18).…”
mentioning
confidence: 99%
“…However, other possible mechanisms, not probed here, may also be contributing toward the superior outcome. BRD4 has also been shown to bind to the acetylated lysine-310 of the RelA subunit of NF-kB and regulate its transcriptional activity (32,33). By inducing RelA acetylation, panobinostat treatment may also increase the BRD4 dependency of the NF-kB activity in AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…BET family proteins (Brd2, Brd3, Brd4, and Brdt) 'read' acK residues on histones and transcription factors (32,33). Brd4 is important in cancer progression (30,31,33), but the role of iNOS in Brd4-mediated cancer progression has not been described previously. In testing our hypothesis, we found that Brd4 is a key co-activator of photostress-augmented iNOS expression.…”
Section: Introductionmentioning
confidence: 99%
“…Using human glioblastoma cells in the present study, we determined that basal and photostress-induced iNOS is regulated by nuclear factor-kappa B (NF-κB). Knowing this and projecting from recently published evidence (30,31), we hypothesized that bromodomain and extra-terminal (BET) protein recognition of ε-N-acetylated lysine residue(s) (acK) on the NF-κB p65/RelA subunit played a key role in iNOS expression. BET family proteins (Brd2, Brd3, Brd4, and Brdt) 'read' acK residues on histones and transcription factors (32,33).…”
Section: Introductionmentioning
confidence: 99%